2022
DOI: 10.3390/cancers14194874
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the DNA Damage Response and DNA Repair Pathways to Enhance Radiosensitivity in Colorectal Cancer

Abstract: Radiotherapy is an important component of current treatment options for colorectal cancer (CRC). It is either applied as neoadjuvant radiotherapy to improve local disease control in rectal cancers or for the treatment of localized metastatic lesions of CRC. DNA double-strand breaks (DSBs) are the major critical lesions contributing to ionizing radiation (IR)-induced cell death. However, CRC stem cells promote radioresistance and tumor cell survival through activating cell-cycle checkpoints to trigger the DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 160 publications
0
16
0
Order By: Relevance
“…60,218,245-251 DNA-PK, ataxia telangiectasia mutated (ATM), ataxia telangiectasia-and Rad3associated kinase (ATR), checkpoint kinase 1/2 (CHK1/2), WEE1, and PARP1 inhibitors are selective radiosensitization of colorectal cancer (CRC) cells. 252 The combination of PARP inhibitors and radiotherapy has entered clinical studies in tumors such as glioma, TNBC, and prostate cancer. 253 In IDH-mutant cancer cells with elevated DNA damage, the SL of PARPi is significantly strengthened by radiation therapy.…”
Section: Sl Drugs Combined With Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…60,218,245-251 DNA-PK, ataxia telangiectasia mutated (ATM), ataxia telangiectasia-and Rad3associated kinase (ATR), checkpoint kinase 1/2 (CHK1/2), WEE1, and PARP1 inhibitors are selective radiosensitization of colorectal cancer (CRC) cells. 252 The combination of PARP inhibitors and radiotherapy has entered clinical studies in tumors such as glioma, TNBC, and prostate cancer. 253 In IDH-mutant cancer cells with elevated DNA damage, the SL of PARPi is significantly strengthened by radiation therapy.…”
Section: Sl Drugs Combined With Radiotherapymentioning
confidence: 99%
“…Synthetic lethal drugs based on tumor‐dependent DNA repair function or DNA stability can widely improve the sensitivity and expand the therapeutic window of chemoradiotherapy and radiotherapy 60,218,245–251 . DNA‐PK, ataxia telangiectasia mutated (ATM), ataxia telangiectasia‐ and Rad3‐associated kinase (ATR), checkpoint kinase 1/2 (CHK1/2), WEE1, and PARP1 inhibitors are selective radiosensitization of colorectal cancer (CRC) cells 252 . The combination of PARP inhibitors and radiotherapy has entered clinical studies in tumors such as glioma, TNBC, and prostate cancer 253 .…”
Section: The Combination Of Antitumor Therapies Based On Slmentioning
confidence: 99%
“…Up to now, many studies have demonstrated that DNA-PKcs inhibitors are radio-and chemotherapyresistant sensitizers for many tumors, such as leukemia, colorectal cancer, etc [23,24]. However, the role of DNA-PKcs in reversing drug resistance in hepatocellular carcinoma remains unclear.…”
Section: Knockdown Of Dna-pkcs Induces Cell Apoptosis and Cell Cycle ...mentioning
confidence: 99%
“…For example, DNA‐PKC deficiency markedly sensitizes tumor cells to IR and enhances IR‐induced tumor suppression in glioblastoma [17]. High‐efficiency and low‐toxicity radiosensitizers targeting the DDR have been developed to enhance the response to radiotherapy in colorectal cancer [18]. Targeting ATR results in selective sensitization of pancreatic tumors to IR in vivo [19].…”
Section: Introductionmentioning
confidence: 99%